Widening interest, widening participation: factors influencing school students’ aspirations to study medicine - Alexander J. Martin; Benjamin J. Beska; Greta Wood; Nicola Wyatt; Anthony Codd; Gillian Vance; Bryan Burford (BMC Medical Education, 2018)
Abstract Background Under-representation of some socio-economic groups in medicine is rooted in under-representation of those groups in applications to medical school. This study aimed to explore what may deter school-age children from applying to study medicine. Methods Workshops were undertaken with school students aged 16–17 years (‘Year 12’, n = 122 across three workshops) and 13–14 years (‘Year 9’, n = 295 across three workshops). Workshops used a variety of methods to identify and discuss participants’ perceptions of medicine, medical school and the application process. Year 12 workshops focused on applications and medical school, while Year 9 took a broader approach reflecting their relative distance from applying. Subsequent workshops were informed by the findings of earlier ones. Results The main finding was that potential applicants had limited knowledge about medicine and medical school in several areas. Older students would benefit from accessible information about medical degrees and application processes, access to work experience opportunities and personal contact with medical students and junior doctors, particularly those from a similar background. Younger students demonstrated a lack of awareness of the breadth of medical careers and a limited understanding of what medicine encompasses. Many Year 9 students were attracted by elements of practice which they did not associate with medicine, such as ‘talking to people with mental health problems’. An exercise addressing this elicited an increase in their interest in medicine. These issues were identified by participants as being more marked for those without knowledgeable support at home or school. It was apparent that school teachers may not be equipped to fill these knowledge gaps. Conclusion Gaps in knowledge and support may reflect the importance of ‘social capital’ in facilitating access to medical school. Medical schools could act as hubs to introduce students to resources which are essential for widening participation. Outreach and support to schools may ensure that fundamental knowledge gaps are equitably addressed for all prospective applicants. More generally, a focus on medicine which under-emphasises aspects of medical practice involving communication may deter some students and have longer term impact on recruitment to careers including general practice and psychiatry.